2015
DOI: 10.1007/s00267-015-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Herders’ “Mental Maps”: Participatory Mapping with Pastoralists’ to Understand Their Grazing Area Differentiation and Characterization

Abstract: Understanding the perception of environmental resources by the users is an important element in planning its sustainable use and management. Pastoralist communities manage their vast grazing territories and exploit resource variability through strategic mobility. However, the knowledge on which pastoralists' resource management is based and their perception of the grazing areas has received limited attention. To improve this understanding and to document this knowledge in a way that can be communicated with 'o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…From 1983, this shift in sketch mapping from geographical knowledge to local knowledge slowly gained momentum through work by Jeremy Shute and David Knight () and then Derek Smith (). It was in the next decade that this vein of research reached its zenith, with a growing body of work in the area by Lydia Teh and colleagues (), Patrick Meyfroidt (), Bor‐Wen Tsai and Yung‐Ching Lo (), J.J. Cockburn and colleagues (), and Hussein Wario and colleagues (), as a few examples (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…From 1983, this shift in sketch mapping from geographical knowledge to local knowledge slowly gained momentum through work by Jeremy Shute and David Knight () and then Derek Smith (). It was in the next decade that this vein of research reached its zenith, with a growing body of work in the area by Lydia Teh and colleagues (), Patrick Meyfroidt (), Bor‐Wen Tsai and Yung‐Ching Lo (), J.J. Cockburn and colleagues (), and Hussein Wario and colleagues (), as a few examples (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In Botswana, Basupi et al [23] used a cognitive mapping process and a participatory GIS approach to assess the effect of land subdivision and privatization on pastoralist grazing patterns and spatial mobility. Other studies have used participatory mapping with Borana pastoralists in southern Ethiopia to determine how resource users perceive their surroundings and choose grazing grounds [22], especially under increased resource sharing [21]. However, despite the reported success of participatory mapping, this approach has rarely been applied in Mongolia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to monitor rangeland use and identify areas with a high risk of degradation, there exist multiple methods from across various disciplines, such as soil and vegetation monitoring [16,20], herd tracking [5,21] and participatory mapping [22,23]. This study focuses on the latter method because participatory mapping has numerous pragmatic advantages to the other methods, along with its ability to directly link individual herd management practices at the community level.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it uses grazing calendar interviews on the last year grazing itinerary and geo-referenced "real time" grazing itineraries to analyse the differences in mobility patterns within and between three different zones of the Borana area experiencing different mobility constraints. Importantly, the study bases its analysis on landscape units identified by pastoralists in participatory resource mapping (Wario et al 2015a) which enables understanding of the organisation and use of grazing resources relevant to herders' grazing management and decision making.…”
Section: Methods Used In the Study Of Pastoral Mobilitymentioning
confidence: 99%
“…Using satellite images of the madda, the participants indicated the location and extent of all grazing units, villages and water sources resulting in a community developed grazing area map. The aim was to understand how the use of the rangelands -already identified into grazing units (Wario et al 2015a) -was organized and how the access is regulated by the community.…”
Section: Data Collectionmentioning
confidence: 99%